Do Demand Curves for Stocks Slope Down? - Shleifer, Andrei (Journal of Finance, 1986)
Since September, 1976, stocks newly included into the Standard and Poor's 500 Index have earned a significant positive abnormal return at the announcement of the inclusion. This return does not disappear for at least ten days after the inclusion. The returns are positively related to measures of buying by index funds, consistent with the hypothesis that demand curves for stocks slope down. The returns are not related to S & P's bond ratings, which is inconsistent with a plausible version of the hypothesis that inclusion is a certification of the quality of the stock.